MENINGKATKAN KEMAMPUAN BERBICARA MELALUI METODE KARYAWISATA PADA ANAK USIA 4-5 TAHUN TK BINTANG KECIL KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Mawar Rosa; Zulkifli N Zulkifli N; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The ability to speak kindergarten children aged 4-5 years Little Star District of Bangko Rokan Hilir, is still low due to lack of child child's ability to speak, through the image of teachers demonstrated in front of the class, children find it difficult to express something in front of the class in explaining the idea of mind to friends -temannya because owned subsidiary vocabulary is still limited. The purpose of this research is to improve speaking skills of children aged 4-5 years Little Star Nursery through metude field. This research is a classroom action research, research data obtained through observation and documentation. This research was conducted through two cycles. In cycle 2 to an increase in the ability to speak the child 81.6%. It can be concluded that by applying the method of field can improve the ability to speak of children aged 4-5 years in kindergarten Little Star District of Bangko Rokan Hilir.Keywords: Speech Kids, Method Leisure